ECONOMIC ANALYSIS OF FACTORS AFFECTING OFF-FARM LABOR SUPPLY IN BAGHDAD GOVERNORATE - Zahraa M. Ali Al-Haboobi, Zahraa M. Ali Al-Haboobi; Eskander. H. Ali, Eskander. H. Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This research aimed to examine how farmers are impacted by risk by estimating the off-farm labour supply model. The study used a qualitative response model to determine the extent to which independent factors influence the dependent factor, using the Probit model. Information was collected randomly from 134 farms it included all crops grown in it of the agricultural divisions of Baghdad Governorate's Karkh and Rusafa sides for the season 2021/ 2022. The research found that the size of the agricultural family is directly proportional to the probability of participating in work outside the farm, as its parameter was 0.015. Also, the higher the educational level of the farmers, the greater the likelihood of participating in work outside the farm. Farm by 0.364. It is also noted that the inverse proportion between the size of the total holding and the percentage of participation in work outside the farm reached 0.011. Likewise, when animal income based on the availability of farm animals increases, it is inversely proportional to the probability of participation in work outside the farm. Therefore, the research recommends reviewing agricultural holding laws, preparing land use maps, reforming small agricultural holding laws and systems, and developing risk management strategies by providing adequate financing and banking facilities.